Expression analysis of defence-related genes in Vitis vinifera cv. Vinhão cell cultures elicited with Phaeomoniella chlamydospora - Lima, M. R. M. (2008)
Esca is a destructive disease that affects Vitis vinífera plants around the world leading to important losses in wine production. Phaeomoniella chlamydospora (Pc) is a fungus frequently associated with esca and grapevine decline. To study the defence response, specifically gene activation, of grapevine to Pc we utilized in vitro cultures of V. vinifera cv. Vinhão (Vv) elicited with fungus extract. The expression of genes encoding pathogenesis‐related proteins (class 6 and class 10 PR proteins, β‐1,3‐glucanase, and class III chitinases) and genes involved in the octadecanoid (lipoxigenase) and phenylpropanoid (phenylalanine ammonia lyase and stilbene synthase) pathways were monitored by semi‐quantitative RT‐PCR.